The psychological mechanisms of spectator experience: a pathway model of immersion, identification, and sport consumption behavior - Chen, Xiaogan; Huang, Zhenxin (Frontiers in Sports and Active Living, 2025)
Amid the growing convergence of experiential economy and contemporary sport contexts, the psychological mechanisms through which immersive experience drives spectator consumption remain insufficiently understood. Grounded in Self-Determination Theory, Social Identity Theory, and Flow Theory, this study proposes a structural pathway model linking immersive experience, team identification, and sport consumption behavior. Motivational regulation type (intrinsic vs. extrinsic) is introduced as a moderating variable to capture variations in the psychological transformation from affective engagement to behavioral intention. Using a questionnaire-based survey, 728 valid responses were collected and analyzed through structural equation modeling and multi-group comparison. The results reveal that immersive experience significantly enhances team identification, which mediates its influence on sport consumption. Moreover, motivational regulation plays a significant moderating role: individuals with high intrinsic motivation are more likely to follow an “immersion → identification → consumption” pathway, while those with extrinsic motivation tend to exhibit a more immediate behavioral response to immersion. These findings advance the theoretical understanding of how spectators transition from emotional engagement to consumer behavior, offering empirical support for the design of immersive sporting experiences and segmented audience management strategies.